Physical modelling as a fundamental tool for the design of harbours and maritime structures - Reis, M. T. (2015)
In this paper, a brief description of the role of physical modelling to support the design of harbours and maritime structures is presented, followed by an example of the tests carried out for the studies of the expansion of Rabo de Peixe fi shing harbour, at São Miguel – Azores. The variety of physical model tests conducted for this case study illustrates the fundamental potential of this modelling technique. The paper ends with some conclusions and future developments on this matter.